Industrial Sustainability and the Circular Economy as Counterparts to the Self-Referral Structure of Natural Law: Part II – A Global Case Study - Fergusson, Lee (Open Science Journal, 2017)
Part I of this two-part series of research papers identified the theoretical foundations of industrial sustainability and circular economy in the structure of Natural Law, as explained by Maharishi Vedic Science. Part I showed that all levels of a manifest hierarchy are governed by self-referral and self-interacting feedback loops, and maintained that the circular economic model represents a counterpart to the self-referral mechanics of Natural Law and is therefore more in accord with Natural Law than the standard linear ‘take, make, dispose’economic model, which is unsustainable due to its attitude to and management of energy and other resource portfolios, waste and end-of-life products. This Part II explores the self-referral structure of Natural Law in the context of one of the world’s largest industrial hazardous wastes: alumina refinery residue or ‘red mud’. The paper examines how this solid waste residue, which is generated at a rate of more than 120 million tonnes each year, can: a) be incorporated into a sustainable, circular economic model in order to reduce waste and improve productivity; and b) be reused or repurposed as either a feedstock to other industrial and municipal processes, such as concrete and cementitious product manufacture, agriculture and mine site rehabilitation, or, if such reuse applications generate other forms of waste, how these, too, can enter further cascading circular economies through beneficial reuse. I propose that a long-term economic and environmental benefit from alumina refinery residue can be liberated when its reuse is based on the principles of self-referral and self-interacting feedback loops as described by Maharishi Vedic Science, and suggest that the deep-rooted commercial, human and environmental risks posed by this industrial waste stream can be minimized or even eliminated through a circular approach to waste management, thereby leading to a more sustainable economic future for the world.